The effect of symphysio-fundal height measurement in detecting macrosomia and predicting shoulder dystocia in Hospital Sultan Ismail, Johor Bahru - Hasan, Hasnurul Juma'ah (2017)
Objective: To assess the diagnostic value of Symphysiofundal height measurement in detecting macrosomia and predicting shoulder dystocia at term. To determine the incidence, risks factors and complications associated with shoulder dystocia. Method:A prospective cross sectional study in Hospital Sultan Ismail was conducted from 1st June 2015 until 30th September 2015 (4 months).The study included 961 pregnant women with singleton fetus completed 37 weeks. Symphysiofundal height measurement was done and the detailsregarding the antenatal review, intrapartum events, immediate postpartum event and neonatal outcome were recorded. The incidence of shoulder dystocia was assessed and risk factors for shoulder dystocia were examined by multiple logistic regression analysis. Results:A total of 961 patients were recruited in this study. Incidence of shoulder dystocia was 0.04% (n=42). The SFH measurement of 40 cm cut-off value for macrosomic babies (birth weight of 4000 g and above) proved to be useful with sensitivity of 78.2% and specificity of 97.9%. While the positive predictive value waspoor at 48.6%, the negative predictive value of 99.4% provided a useful indicator. The incidence of shoulder dystocia rose with increasing SFH measurement (2 to 6 fold) and birthweight (3 to 7 fold). When the SFH (≥ 40cm), the incidence of shoulder dystocia was 13.5% (5/37) as compared to 2.3% (17/735) when SFH (< 39cm) and 16 %( 20/126) with SFH (>39cm but <40cm) respectively. When the birth weight ≥ 4000gram, the incidence of shoulder dystocia was 21.7% (5/23) and the association was also noted when birth weight ≥ 3800 to 3990gram group (29.3%). The incidence noted to be increased from the universal (4.0%) starting with the birth weight ≥ 3600gram. A total of 21 babies admitted to NICU with 5 of them with incomplete Moro Reflex and 2 with low Apgar score. There was one case of maternal third degree perineal tear. Conclusion: The 40 cm cut-off for macrosomic babies (birth weight of 4000 g and above) proved to be useful with sensitivity of 78.2% and specificity of 97.9%. Although the overall incidences of macrosomia and shoulder dystocia were low, the risk of shoulder dystocia was strongly linked to increasing birthweight and SFH measurement. The only reliable risks factors associated with shoulder dystocia in this study were symphysio fundal height measurement more than 40cm (n=5, 11.9%) and birth weight more than 4000 gram. (n=5, 11.9%). However shoulder dystocia can occur at SFH measurement ≥37cm and birth weight of ≥3600gram.International guidelines for elective caesarean delivery in suspected cases of macrosomia may not, therefore, apply to Malaysian population.